Development and Integration of Microgrids 2017
DOI: 10.5772/intechopen.68894
|View full text |Cite
|
Sign up to set email alerts
|

Operation of Plug-In Electric Vehicles for Voltage Balancing in Unbalanced Microgrids

Abstract: The widespread use of distributed energy resources in the future electric distribution systems represents both a challenge and an opportunity for all the Smart Grid operators. Among these resources, plug-in electric vehicles are expected to play a significant role not only for the economic and environmental benefits they involve but also for the ancillary services they can provide to the supplying grid. This chapter deals with realtime operation of unbalanced microgrids including plug-in electric vehicles. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 40 publications
0
2
0
Order By: Relevance
“…The authors of [ 21 ] concluded that V2G technology could enhance the coordination between the HMG sectors. The utilization of EV batteries to balance an unbalanced microgrid was introduced in [ 22 ]. Mortaz and Valenzuela [ 23 ] utilized Bender’s decomposition to calculate the operational costs to find the optimal size and number of the V2G parking lots via Nelder–Mead optimization algorithm with conclusions that V2G had enhanced the long-term electricity cost.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The authors of [ 21 ] concluded that V2G technology could enhance the coordination between the HMG sectors. The utilization of EV batteries to balance an unbalanced microgrid was introduced in [ 22 ]. Mortaz and Valenzuela [ 23 ] utilized Bender’s decomposition to calculate the operational costs to find the optimal size and number of the V2G parking lots via Nelder–Mead optimization algorithm with conclusions that V2G had enhanced the long-term electricity cost.…”
Section: Introductionmentioning
confidence: 99%
“…As discussed above, some existing approaches optimize economic operations by building exhausting stochastic models, e.g., [ 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 ]. Others take an easier way of considering entire EVs battery resources as passive loads, e.g., [ 27 , 28 , 29 , 30 , 31 , 32 ], burning up a valuable energy compensation resource in rush hours.…”
Section: Introductionmentioning
confidence: 99%